Effects of carbamazepine on hepatic glutathione level in rats and determination of carbamazepine and its epoxide metabolite in plasma by HPLC - (:unkn) unknown (Walter de Gruyter GmbH, 1998)
We investigated whether carbamazepine, which is known to be metabolized to an electrophilic epoxide derivative in the body, causes any decrease, analogous to the action of epoxides, of hepatic glutathione (GSH) level in rats. Carbamazepine was administered to rats and liver GSH levels were determined spectrophotometrically. Neither a single low nor repeated low doses (30 mg/kg) of carbamazepine (CBZ) produced a statistically significant difference in GSH levels relative to controls. A single high dose of CBZ (100 mg/kg) produced a large and significant decrease relative to control (GSH level 3.82 ± 0.64 vs 6.54 ± 0.45 μmol GSH/g liver). CBZ and its metabolite carbamazepine-10,11-epoxide were determined in plasma by HPLC after the high dose of carbamazepine administration. The concentrations of carbamazepine and carbamazepine-10,11-epoxide were 18.9 ± 2.9 μg/ml and 10.7 ± 2.8 μg/ml, respectively.
Keywords: Carbamazepine; Carbamazepine-10,11-epoxide; Glutathione; HPLC; Liver